FLEXURAL BEHAVIOR OF ALIGNED STEEL REINFORCED CONCRETE BEAMS - Fatima Aboud (Misan Journal of Engineering Sciences)
:The configuration of the steel reinforcement is investigated in this work in connection to the flexural behavior of reinforced concrete beams(RC beams).Employing unique steel reinforcement configurations allowed for the investigation of the influence that the shape of the steel has on the parameters of the concrete beam, such as the cracking load, ultimate load, load-deflection curve , ductility, and energy absorption. Seven beams were manufactured in all, and they were divided in to two groups: those that supported the concrete beams with curved steel bars, and those that used triangular steel reinforcement. Several bars of curved and triangle reinforcement were employed, with two, three, and five bars being utilized.The flexural behavior of reinforced concrete beams was found to be affected by the presence of curved and triangular steel reinforcement, according to research. The curved steel reinforcement not only increased the flexural strength but also significantly enhanced the ultimate load-bearing capacity. Additionally , the cracking strength was marginally increased as a result of the reinforcement. On the other hand, the cracking strength was significantly lower and the final flexural strength was significantly higher for steel bars that were organized in a triangle . In contrast to the triangular form, which showed a decrease in the cracking load of 4.2%-7.1% and an increase in the ultimate load of 7.8%-8.15%, the cracking load increased from 5.7% to 8%, and the ultimate load climbed from11.4% to 32%.Both of these changes were accomplished by increasing the ultimate load.The ductility of the steel as well as its capacity to absorb energy were both enhanced by the modification of its configuration